PD Measurement Under Direct and Impulse Voltage Stress Conditions - Norasage Pattanadech; Rainer Haller; Stefan Kornhuber; Michael Muhr (My University, 2023)
In the last decades applications such as direct voltage (DC) and impulse voltage stress conditions have increased and require quality testing methods and procedures to provide reliable operation of applied components within electrical power systems. This chapter discusses the options and issues for electrical partial discharge (PD) measurement under DC and impulse stress conditions. Before discussing the PD behavior and derived requirements and conditions at assumed DC, it should be noticed that at insulation stress under DC not only the steady-state DC field conditions have to be considered. The standardized classical impulse test voltages – lightning-, switching-, or oscillating impulse – are introduced in quality-testing procedures for high-voltage insulation equipment. It is obvious that PD should be measured even under such conditions as a well-proven quality assessment tool.
Keywords: Impulse generator; High Voltage; High voltage insulation and dielectric phenomena